2018
DOI: 10.1111/eva.12647
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of the introduced and cultivated Pacific kelp Undaria pinnatifida: Marinas—not farms—drive regional connectivity and establishment in natural rocky reefs

Abstract: Ports and farms are well‐known primary introduction hot spots for marine non‐indigenous species (NIS). The extent to which these anthropogenic habitats are sustainable sources of propagules and influence the evolution of NIS in natural habitats was examined in the edible seaweed Undaria pinnatifida, native to Asia and introduced to Europe in the 1970s. Following its deliberate introduction 40 years ago along the French coast of the English Channel, this kelp is now found in three contrasting habitat types: far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 97 publications
(152 reference statements)
11
72
0
Order By: Relevance
“…In seemingly “open” marine systems, the relative influence of both types of dispersal is however expected to differ according to pelagic dispersal duration, with a putative larger influence of human‐mediated dispersal for species characterized by short‐lived dispersal stage. This expectation has been supported by genetic studies of short dispersers, such as the tunicate Ciona intestinalis (Hudson, Viard, Roby, & Rius, ) or the Pacific kelp Undaria pinnatifida (Guzinski, Ballenghien, Daguin‐Thiébaut, Lévêque, & Viard, ): in marinas, these species display chaotic genetic structure at regional scale, which is best explained by the role of shipping than natural dispersal. The influence of human‐mediated dispersal may however be less important in marine invertebrates displaying larval stage lasting typically 3–5 weeks in the water column (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…In seemingly “open” marine systems, the relative influence of both types of dispersal is however expected to differ according to pelagic dispersal duration, with a putative larger influence of human‐mediated dispersal for species characterized by short‐lived dispersal stage. This expectation has been supported by genetic studies of short dispersers, such as the tunicate Ciona intestinalis (Hudson, Viard, Roby, & Rius, ) or the Pacific kelp Undaria pinnatifida (Guzinski, Ballenghien, Daguin‐Thiébaut, Lévêque, & Viard, ): in marinas, these species display chaotic genetic structure at regional scale, which is best explained by the role of shipping than natural dispersal. The influence of human‐mediated dispersal may however be less important in marine invertebrates displaying larval stage lasting typically 3–5 weeks in the water column (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Given the presence of marinas in the vicinity of the large studied ports and their colonisation by dock mussels, they constitute a possible way of secondary expansion at a regional scale. Indeed, marinas and associated activities, for example leisure boating, have been shown to contribute to regional NIS expansion (Clarke Murray, Pakhomov, & Therriault, 2011) and create chaotic genetic structure in both native and non-native species inhabiting these artificial habitats (Guzinski, Ballenghien, Daguin-Thiébaut, Lévêque, & Viard, 2018;Hudson, Viard, Roby, & Rius, 2016). For now, in the Bay of Brest, only the marinas close to the large port contained dock mussels.…”
Section: The Introduction Of Dock Mussels and The Timing Of Admixturementioning
confidence: 99%
“…However, the most striking result was the absence of genetic diversity across 14 microsatellite markers over more than 1,000 samples from both introduction ranges ( Figure 1). This lack of diversity contrasts sharply with other seaweed cases: for instance, a recent study by Guzinski et al (2018) showed that a dozen microsatellites provided roughly similar results as several thousand SNPs obtained from ddRAD sequencing to analyze the connectivity and adaptation processes in the introduced seaweed U. pinnatifida, at a regional scale. So far, introduced populations of sexually reproducing marine invaders have never been shown to be monomorphic at microsatellites or similar type of highly variable markers.…”
Section: A Poorly Diverse But Successful Introduced Speciesmentioning
confidence: 74%